2012
DOI: 10.1089/ars.2011.4090
|View full text |Cite
|
Sign up to set email alerts
|

Cyanate Is a Novel Inducer of Endothelial ICAM-1 Expression

Abstract: Collectively, our data raise the possibility that cyanate amplifies vascular inflammation, linking inflammation, smoking, and uremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
33
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 40 publications
8
33
1
Order By: Relevance
“…A significant reduction in migration of the cyanate‐treated endothelial cells was observed, as was impairment of both proliferation and tube formation. This result is consistent with recent data showing that cyanate itself amplifies vascular inflammation . Our in vitro study suggested that cyanate impaired angiogenesis by at least 2 mechanisms: (1) direct effects on endothelial cells, and (2) indirect effects by promoting protein carbamylation.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A significant reduction in migration of the cyanate‐treated endothelial cells was observed, as was impairment of both proliferation and tube formation. This result is consistent with recent data showing that cyanate itself amplifies vascular inflammation . Our in vitro study suggested that cyanate impaired angiogenesis by at least 2 mechanisms: (1) direct effects on endothelial cells, and (2) indirect effects by promoting protein carbamylation.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, the impaired tissue perfusion induced by cyanate might be mediated in part by the attenuation of endothelial angiogenic function. Similarly, recent studies have demonstrated endothelial dysfunction and reduced endothelial nitric oxide synthase in cyanate‐treated mice . Our results, combined with others, suggest that exposure to cyanate in vivo could impair endothelial function.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…24,48 Carbamylation of high-density lipoprotein (HDL) similarly appears to confer atherogenic properties, 74 and there are studies suggesting that cyanate itself has direct pathologic effects on endothelial cells. 75,76 Most recently, epidemiologic studies have further established protein carbamylation as an independent risk factor for all-cause mortality and death from cardiac causes in both uremic and non-uremic populations (see Figure 2 and Recent Advances). 2,62,77 …”
Section: Pathogenesismentioning
confidence: 99%
“…Levels of total cholesterol, nonesterifi ed cholesterol, triglycerides, choline-containing phospholipids (Diasys, Holzheim, Germany), sphingomyelin (Cayman Europe, Tallinn, Estonia), and lysophosphatidylcholine (LPC) (Cosmo Bio Co. LTD, Tokyo, Japan) were measured enzymatically ( 15,22 ). Sphingomyelin values were subtracted from total choline-containing phospholipids to quantify phosphatidylcholine.…”
Section: Determination Of Plasma and Hdl-lipid Compositionmentioning
confidence: 99%